Kill Bill. Volume 1 [videorecording (Blu-Ray)] - Tarantino, Quentin; Thurman, Uma; Liu, Lucy, 1968-; Fox, Vivica A., 1964-; Madsen, Michael; Hannah, Daryl; Carradine, David; Chiba, Sonny, 1939-2021; Dreyfus, Julie, 1966-; Kuriyama, Chiaki, 1984-; Liu, Chia Hui; Parks, Michael, 1940-2017 (Miramax Home Entertainment : Distributed by Buena Vista Home Entertainment, 2008)
Four years after taking a bullet in the head at her own wedding, the bride emerges from a coma and decides it's time for payback ... with a vengeance. Having been gunned down by her former boss and his deadly squad of international assassins, it's a kill-or-be-killed fight. She didn't start this deadly series of events, but she is determined to finish the business.